Computer-mediated communication vs. face-to-face communication : a test of the hyperpersonal communication model. - Lee, Bee Hian. (2008)
A total of 48 zero-history participants were grouped into dyads and asked to cooperate on low- and high-equivocality tasks over a series of three meetings conducted on three consecutive days. The effects of gender and group composition were also explores.